DISTILLATION OF ESSENTIAL OILS FROM THE LEAVES AND STEMS OF CITRONELLA (Cymbopogon Winterianus) USING A SOLAR ENERGY-BASED VAPOR DISTILLATION APPARATUS WITH PHOTOVOLTAIC METHOD - Hafidh, Muhammad; Rihayat, Teuku; Elwina, E (Jurnal Sains dan Teknologi Reaksi, 2023)
The photovoltaic method with solar panel modules with a capacity of 100 Wp can absorb heat and convert it into electrical energy up to 100 watts / hour and is used for the citronella oil refining process which requires 57,550 Kj of energy.  By using 4 solar cell panels, within 4 hours the power generated is able to meet these energy needs. Based on the test results of the design of the distillation device using solar cells, the efficiency of energy absorption cannot be absorbed up to 100%, due to the occurrence of lost energy but this can be overcome with a longer absorption time. In testing citronella oil with variations in drying time and distillation time, it was found that the optimum time to produce the highest percentage of citronella oil yield was at a drying time of 18 hours with a distillation time of 6 hours, namely 1.20%. From the laboratory tests produced, citronella oil with variations in drying time and operating time has a density value ranging from 0.8751gr/ml to 0.8831gr/ml and the best GC-MS test results obtained the amount of citronellol in the sample as much as 15.73% and the amount of geraniol as much as 28.57% has met the Indonesian National Standard (SNI) 2385-2006.Keywords: Solar Cell, Photovoltaic, Citronella Oil, Solar Panel